Predicting Leadership Competency Development and Promotion Among High-Potential Executives: The Role of Leader Identity - Kragt, Darja; Day, David V. (Frontiers in Psychology, 2020)
We propose that distinct leadership competencies differ in their development over time. Extending the integrative model of leader development (Day, Harrison, & Halpin, 2009), we further propose that leader identity will form complex relationships with leadership competencies over time. To test these propositions, we use longitudinal data (i.e., five month, four measurement points) of the 80 in total high-potential executives in a corporate leadership development program. We find significant difference in the initial levels and changes of eight distinct leadership competencies. We also find that leader identity relates to the development of certain – but not all -- leadership competencies. Finally, we demonstrate the importance of developing leadership competencies by linking them to career advancement (i.e., job promotion). These findings are discussed in light of their theoretical and practical implications.